Financial Globalization and the New Capitalism - Ion Bucur (Theoretical and Applied Economics, 2009)

(untitled)
Financial globalization, a complex phenomenon that has multiple facets, is directly influenced by some aspects characterizing the current stage of capitalism. In order to decrypt the set of such interferences, the consequences have been emphasized of the excessive trust in the market mechanisms, the role of deregulation and liberalization in promoting a new economic direction, as well as other theses representing the essence of neo-liberal revolution. The realities specific to the last three decays of the 20th century generated enhanced criticism regarding the myth of pure and perfect transparency, the market inability of self-regulation and the illusion of perfect information. The excesses of neo-liberalism imposed the need for a new paradigm, concretized in the mutations in the nature and mechanisms of capitalism, the domination of finances and knowledge, a paradigm in which market globalization and financial profitability logic are becoming priorities. In the second part of the article the conditions are analyzed that favored the occurrence and expansion of financial globalization, as well as the multiple implications of such over the micro and macro-economical mechanisms. A particular focus is on describing the characteristics of financial globalization in the current phase: the occurrence of new financial players (institutional investors) and tools, markets de-localization and un-intermediated financial operations. As a conclusion, the tendencies are noticed of the financial world economy to become fragile, of fading connections between the financial and the real economy, of enhanced risk for financial accidents to propagate. Based on these observations, the extent is emphasized to which financial globalization provides the possibility of the financial crises to occur and expand.